Rational design of antimicrobial peptides targeting Gram-negative bacteria. (June 2021) - Huynh, Loan; Velásquez, Jeanette; Rabara, Roel; Basu, Supratim; Nguyen, Hau B.; Gupta, Goutam
Graphical abstract: Highlights: Terminal carboxyl capping enhances both membrane insertion and antibacterial activity. Lysine-to-arginine substitutions can revitalize the antimicrobial activity against a strain of E. coli with evolved resistance to P1. Cocktails of closely related AMPs may be useful in overcoming evolved resistance. Abstract: Membrane-targeting host antimicrobial peptides (AMPs) can kill or inhibit the growth of Gram-negative bacteria. However, the evolution of resistance among microbes poses a substantial barrier to the long-term utility of the host AMPs. Combining experiment and molecular dynamics simulations, we show that terminal carboxyl capping enhances both membrane insertion and antibacterial activity of an AMP called P1. Furthermore, we show that a bacterial strain with evolved resistance to this peptide becomes susceptible to P1 variants with either backbone capping or lysine-to-arginine substitutions. Our results suggest that cocktails of closely related AMPs may be useful in overcoming evolved resistance.